Pengaturan Sanksi Pidana Bagi Pelaku Pembakaran Hutan - Sang Bagus Nyoman Wahyuda Putra; I Nyoman Gede Sugiartha; Luh Putu Suryani (Jurnal Preferensi Hukum, 2021)
The base burning which is getting more and more massive every year in the archipelago because of the large number of land clearing by burning forests. For this reason, the burning of the widening of the plinth can cause natural destruction to disturb the fitness of the residents, to be quietly located, and to obtain a good and fit nature of life, which is the feasibility of such citizens as voiced in Article 28 h paragraph (I) of the 1945 Constitution of the Republic of Indonesia. The purpose of this study was to determine the legal arrangements for forest burning agents and to know the criminal sanctions for forest fire offenders. The method used in the preparation of this research is a normative legal study using a problem study using a legal basis that applies to laws and regulations contained in the literature. The method used for the following research is juridical normative, analytical descriptive in nature, and using the statutory regulation scheme, the executor of the scorching action of bases and land that continuously carries out scorching grounds should be carried out under criminal law, civil law in the form of penalties and administrative law takes the form of abolishing the business permit management permit. Law Number 41 Year 1999 Law Number 19 Year 2004 regarding Reason, Law Number 32 Year 2009 regarding Environmental Protection and Management, Civil Code, Criminal Code and Legal Code The administration, in fact, is unable to make a sense of the craving for the executors of the crime of burning forests and land who carry out scorching of bases and land because there is still a problem of burning the base.